Professional Competencies of Teachers of Foreign Languages - B. Evangeline Priscilla; A. V. Konobeiev (Дискурс профессиональной коммуникации, 2022)
The article considers the changes that have been taking place in the world in recent years, including a growing demand for soft skills, and the impact these changes may have on the professional competencies of teachers of the English language worldwide. The authors explore professional standards and requirements for teachers in a number of countries, including Canada, the EU, Russia, and India in order to see whether these changes are reflected, and describe the teaching context in India to see what teachers are concerned with. The article shows that although digital competencies are included in the teachers’ competencies in many countries, certain expectations of learners and their potential employers are not reflected in frameworks of teacher competencies and requirements. The authors believe that current frameworks of teachers’ competencies in general and English language teachers’ competencies, in particular, need a partial revision to accommodate the expectations of learners and their potential employers, which may lead to a more interdisciplinary approach to teacher training.